2014
DOI: 10.1186/1470-7330-14-16
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic myocardial metastasis from cancers of upper aero-digestive tract detected on FDG PET/CT: a series of 4 cases

Abstract: Metastatic involvement of the heart is a rare occurrence and remains undiagnosed until autopsy. In some instances, patients may have cardiac symptoms, leading to ante-mortem diagnosis. Although most primary cancers have been documented to metastasize to heart, the existing literature on cancers of upper aero-digestive tract is an exception, with only a few reports. We report four cases of upper aero-digestive tract cancers, three of which arise from oral cavity, one from lower esophagus, metastasising to the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In a large study of postmortem patients with a known malignancy, Bussani et al reported a 9.1% overall incidence of cardiac metastases with only 5.3% (4 out of 75) secondary to oral cavity cancer compared to 48.4% secondary to mesothelioma, 27.8% to melanoma, and 21.0% to lung adenocarcinoma [2]. Four different mechanisms have been postulated by which cancer spreads to the heart, including direct extension, hematologic spread, lymphatic spread, and intracavitary diffusion via the inferior vena cava or pulmonary veins [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large study of postmortem patients with a known malignancy, Bussani et al reported a 9.1% overall incidence of cardiac metastases with only 5.3% (4 out of 75) secondary to oral cavity cancer compared to 48.4% secondary to mesothelioma, 27.8% to melanoma, and 21.0% to lung adenocarcinoma [2]. Four different mechanisms have been postulated by which cancer spreads to the heart, including direct extension, hematologic spread, lymphatic spread, and intracavitary diffusion via the inferior vena cava or pulmonary veins [24].…”
Section: Discussionmentioning
confidence: 99%
“…Current National Comprehensive Cancer Network (NCCN) guidelines do not recommend the use of routine follow-up imaging unless clinically indicated and no evidence to demonstrate a benefit of surveillance imaging after 6 months [11]. However, multiple case reports have reported that the use of PET/CT may lead to improved accuracy and earlier detection of cardiac metastases in patients with head and neck cancer [4, 1215]. Some studies have suggested that routine ECG may have a diagnostic value, but findings are often nonspecific, and further confirmation with imaging would be required [1517].…”
Section: Discussionmentioning
confidence: 99%
“…[2] Even though they can cause some symptoms, cardiac metastases frequently stay asymptomatic in the initial stage of the disease and therefore remain undetected. [3] A few reports showed that 18 F-fluorodeoxyglucose positron-emission tomography/computed tomography ( 18 F-FDG PET/CT) scan was useful in detection of cardiac metastases from various primary malignancies. [47] However, multiple cardiac metastases detected by 18 F-FDG PET/CT have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Four hypotheses have been believed for cardiac metastases, those include direct extension, hematologic spread, lymphatic spread, and intracavitary diffusion via the inferior vena cava or pulmonary veins. [ 1 2 3 ] As to primary skin malignancies, there are several reports of metastatic malignant melanoma in the myocardium;[ 4 ] however, there are only a few published case reports of metastatic squamous cell carcinoma (SCC) to the heart. [ 5 6 7 8 ] With the increasing use of PET-CT in oncology, asymptomatic cardiac metastases are now getting detected more frequently.…”
mentioning
confidence: 99%
“…[ 5 6 7 8 ] With the increasing use of PET-CT in oncology, asymptomatic cardiac metastases are now getting detected more frequently. Reports of cardiac metastases on PET/CT are seen in melanoma,[ 9 ] Ewing's sarcoma,[ 10 ] renal cell carcinoma,[ 11 ] breast cancer,[ 12 ] upper aero-digestive tract,[ 3 ] head-and-neck cancer,[ 13 ] carcinoma rectum,[ 14 ] to name a few, with no reports from cutaneous SCC. Our case is a valuable addition to the existing literature on myocardial metastases and also highlights the role of FDG PET/CT in the detection of such rare sites, especially in asymptomatic patients, which otherwise would have been undiagnosed.…”
mentioning
confidence: 99%